KENDALA-KENDALA GURU DALAM MENERAPKAN PENGELOLAAN KELAS PADA PEMBELAJARAN IPS TERPADU KELAS VIII DI SMP NEGERI 4 TARUSAN KABUPATEN PESISIR SELATAN - Yulianis, Yulianis; Husnita, Liza; Meldawati, Meldawati (Pendidikan Sejarah, 2014)
Â This research is motivated by the problem of classroom management implemented teacher has not gone well. On the basis of the problem of this research is focused on the constraints of teachers in implementing Classroom Management in Integrated Social learning in SMP Negeri 4 Tarusan Pesisir Selatan Region. This study aims to determine the constraints of teachers in implementing Classroom Management in Integrated Social learning in SMP Negeri 4 Tarusan Pesisir Selatan Region, views from the skills associated with the creation and maintenance of learning conditions, divide the attention of students, management teachers in focus groups or class, giving clear instructions to students, reprimand or termination and provide reinforcement to the students. Based on these problems, the method used in this study is the evaluation study. To test the validity of the data the authors used data triangulation. Then the techniques of data analysis in this study using the interactive analysis technique proposed by Huberman Milles, which consists of data collection, data reduction, data display and conclusion. The results show the obstacles faced by teachers in classroom management are: students lack discipline, too many students, students who have a good personality and lack of discipline less, give clear instructions for materials that are difficult to understand by students, students who have personalities less good and less discipline and character of the students come from diverse backgrounds as different. It can be concluded that the Integrated Social Science teachers have the classroom management problems, especially problems related to students. This happens because of the diversity of characteristics possessed by students.